2018
DOI: 10.1136/bmjopen-2017-020530
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clustering of cardiovascular risk factors: a cross-sectional survey among Nanjing adults in China

Abstract: ObjectivesTo estimate prevalence and clustering of cardiovascular risk factors (CRFs), and investigate the association between relevant characteristics and CRF clustering among adults in eastern China.DesignCommunity-based cross-sectional study.SettingData were collected by interview survey, physical measurements and laboratory examinations from the 2011 Nanjing Chronic Disease and Risk Factor Surveillance.ParticipantsA representative sample of 41 072 residents aged ≥18 years volunteered to participate in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
34
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 38 publications
11
34
5
Order By: Relevance
“…The major finding of this study was that the prevalence of CVD biological risk factors was fairly high with a tendency of clustering. Several previous epidemiological studies reported the clustering of CVD biological risk factors in Chinese populations 20–22. For example, the Chinese Physiological Constant and Health Condition survey measured CVD risk factors in a nationally representative sample of 23 010 Chinese aged 18 or older and provided the best comparison data for our study 20.…”
Section: Discussionmentioning
confidence: 99%
“…The major finding of this study was that the prevalence of CVD biological risk factors was fairly high with a tendency of clustering. Several previous epidemiological studies reported the clustering of CVD biological risk factors in Chinese populations 20–22. For example, the Chinese Physiological Constant and Health Condition survey measured CVD risk factors in a nationally representative sample of 23 010 Chinese aged 18 or older and provided the best comparison data for our study 20.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, total risk of CVD is the sum of respective risks arising from the incidence of major CRFs. [10][11][12][13][14] The estimated risk of a CVD increases with the emergence of an additional CRF. 15 Age is also frequently allocated into the same category.…”
Section: Introductionmentioning
confidence: 99%
“…This population-based, cross-sectional study was carried out between June and November 2011 from the Chronic Disease and Risk Factor Surveillance in Nanjing, the capital of Jiangsu Province in east of China. The survey has been described in details previously [17]. Briefly, the inclusion criteria for sample population in our study were native permanent residents aged 18 years and above, who lived in local villages/communities for at least 6 months.…”
Section: Study Participantsmentioning
confidence: 99%